Studies of Adsorption of Heavy Metals onto Spent Coffee Ground: Equilibrium, Regeneration, and Dynamic Performance in a Fixed-Bed Column - N. E. Davila-Guzman; F. J. Cerino-Córdova; M. Loredo-Cancino; J. R. Rangel-Mendez; R. Gómez-González; E. Soto-Regalado (International Journal of Chemical Engineering)
Equilibrium and dynamic adsorption of heavy metals onto spent coffee ground (SCG) were studied. The equilibrium adsorption of Cd2+, Cu2+, and Pb2+ in a batch system was modeled by an ion-exchange model (IEM) based on an ion-exchange of heavy metals with calcium and protons bonded to active sites on SCG surface. The maximum amount of adsorbed metal ions obtained using the IEM was 0.12, 0.21, and 0.32 mmol/g of Cd2+, Cu2+, and Pb2+, respectively. Regeneration of SCG was evaluated using citric acid, calcium chloride, and nitric acid. The observed trend of desorption efficiency through four adsorption-desorption cycles was HNO3 > CaCl2 > C6H8O7. The effect of process variables such as flow rate and bed height during the dynamic adsorption was evaluated. Moreover, the applicability of a mass transfer model based on external mass transfer resistance, axial dispersion, and ion-exchange isotherm was evaluated, and the results were in good agreement with the experimental data for the adsorption in SCG packed column. The sensitivity analysis of the model parameters showed that axial dispersion coefficient is the most significant parameter in the dynamic simulation. The results obtained showed the potential of SCG as a low-cost material for wastewater metal removal in continuous systems.